Photothermal conversion of biodegradable fluids and carbon black nanofluids - Anna Kosinska; Boris V. Balakin; Pawel Kosinski (Scientific Reports, 2022)
Abstract The paper is devoted to the topic of direct absorption solar collectors (DASCs). Various kinds of fluids can be used as heat transfer fluid in DASCs, and the main focus of our paper is on comparing nanofluids (water with carbon black nanoparticles, concentrations between 0.25 and 1.00% weight) and biodegradable coffee colloids. At first, these fluids were tested by exposing them to irradiation caused by artificial light in indoor experiments, and the corresponding temperature increase was recorded. The fluids were placed in a beaker with a relatively large size so that most of the fluid was not directly irradiated. In these experiments, the performance of the two studied fluids was similar: the resulting temperature increase varied between 46 and 50 °C. Our next experiments involved a smaller system subjected to irradiation obtained by using a solar collector. As a result, we detected an intense absorption on the nanoparticle surface so that the temperature rise in the nanofluid was higher than in the coffee colloids. Next, the process was analysed using a theoretical analysis that gave good correspondence with the experiments. Finally, we extended the theoretical analysis to a DASC with a flowing fluid. The model was validated against results from the literature, but it also supported our experimental findings.